O debate enfraquecido: o desânimo dos educadores diante da realidade cotidiana das escolas - Buffa, Maurício (Universidade Federal de São Carlos, 2014)
This thesis was inspired in the professors Paolo Nosella and Ester Buffa s research, A Educação Negada , a paper about the great debates which permeated Brazilian education throughout the 20th century. However, unlike the masters, she did not lean on the opinion of any great exponent, limiting to observe if teachers, principals and pedagogic coordinators currently participates, resist or only accompany the various everyday debates that permeate not only the most theoretical issues of education, but also characteristics and particularities of the educational system and the operation and management of the school systems structures. To achieve this aim, the research focused on two municipal schools from Cristais Paulista, in São Paulo. During almost 2 years, 62 educators were approached through semi-structured interviews, informal conversations and questionnaires. The study also used on-site observation, with the participation of this researcher in the HTPC meetings (pedagogic meetings where the teachers work as a group on the discussion and analysis of educational issues). Based on the assumptions of Oral History, and believing that doxa is the fertile ground for the emergence of episteme, the research stressed the opinion of the interviewed educators, adding them to the observations and collected data. Facing the inability to discern which would be the most true, it was listened as much as possible and considered the most probable not as ways to possible solutions, but simply to understand the context in which these teachers navigate. As stages of this investigation, it was sought, in first place, to understand how was the formation of the Brazilian State and the influence of this process in the formation and development of our society, which allowed us to see its authoritarian and little opened to debate feature. In a second moment, the paper endeavored to trace some of the main theoretical debates that have developed in our educational history, trying to show the main currents that disputed the primacy in our educational system. In this way, it was found that nowadays teachers are very distant from an effective participation in the main debates that permeate current Brazilian education. In general, they seem not to worry with the theories that, despite their understanding, end up guiding their way of teaching. Beyond that, they seem unwilling to the theories that discuss the role of schools and the currents that debate the best way to manage them. In the end, and with no concern to conclude, this study leaves as a proposal to improve Brazilian education the idea to heavily invest in a more beautiful and pleasant school, with teachers working full time and with more administrative, financial and pedagogic autonomy.
O debate enfraquecido: o desânimo dos educadores diante da realidade cotidiana das escolas
The weakened debate: the teacher s discouragement due to the everyday reality in schools
Keywords: Professores; Discussões e debates; Escolas - organização e administração; Teorias pedagógicas; Debate; Teachers; School administration; Pedagogic theories; CIENCIAS HUMANAS::EDUCACAO